In situ chalcophile and siderophile element behavior in sulfides from moroccan middle atlas spinel peridotite xenoliths during metasomatism and weathering - Westner, Katrin; Beier, Christoph; Klemd, Reiner; Osbahr, Inga; Brooks, Nadine (Minerals, 2019)
In situ chalcophile and siderophile major and trace elements were analyzed in sulfides from eight Moroccan Middle Atlas lherzolite xenoliths using electron microprobe and laser ablation inductively coupled plasma mass spectrometry. The sulfides occur enclosed in primary silicates, interstitial in the peridotite matrix, and associated with glass-bearing melt pockets. Monosulfide solid solutions are enriched in these xenoliths relative to pentlandite and intermediate solid solutions. Regardless of the textural occurrence, sulfide platinum-group element (PGE) patterns are distinguished into residual ([Pd/Ir]N < 1 and [Pt/Pd]N > 1 or [Pt/Pd]N < 1), melt-like ([Pd/Ir]N > 1), and unfractionated patterns. The coexistence of both residual and melt-like PGE signatures on a cm scale in a single sample implies that sulfides may record initial depletion and subsequent re-enrichment more effectively than constituent silicates do. Chalcophile and siderophile trace elements other than the PGEs are fractionated between the precipitated sulfide phases, but do not vary systematically with the PGE signatures, suggesting that the PGEs are comparatively sensitive to melting and depletion. In addition, Fe-rich hydroxides generated by sulfide breakdown due to atmospheric weathering display PGE systematics almost identical to their precursor sulfides, implying that they may be reliable tracers of mantle processes even after extensive weathering.
CRIS-Team Scopus Importer:2019-06-21
Keywords: Metasomatism; Middle atlas; Platinum-group elements; Subcontinental lithospheric mantle; Sulfides; Xenoliths